2011
DOI: 10.4236/ce.2011.21007
|View full text |Cite
|
Sign up to set email alerts
|

Discussion Article: Disciplinary Boundaries for Creativity

Abstract: Creativity is a very topical issue and indeed a political one. For example, the very notion of ‘little c creativity’ seems to be a reflection of the requirements of what could be described as a ‘Post-Fordist’ economy. However, the call to develop creativity in education is largely based on the idea of creativity as the production of novel ideas. The central argument of this article is that creativity cannot be seen purely in terms of novel ideas but that it is intrinsically bound with the teaching of the acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
0
11
0
3
Order By: Relevance
“…Again, the old saying that creativity is 1% inspiration and 99% perspiration should be noted (Rowlands, 2011).…”
Section: The Equationmentioning
confidence: 99%
“…Again, the old saying that creativity is 1% inspiration and 99% perspiration should be noted (Rowlands, 2011).…”
Section: The Equationmentioning
confidence: 99%
“…Furthermore, mathematical creativity ensures the growth of the field of mathematics as a whole (Sriraman, 2009). A first step towards achieving this goal is to assist teachers to view creativity as inherent in learning (Beghetto & Kaufman, 2009), and to inspire teachers to believe that all students can become creative, as creativity is not an exclusive trait of the gifted (Rowlands, 2011).…”
Section: Conclusion and Implications For The Futurementioning
confidence: 99%
“…From the overall perspectives of research in creativity and creative education, Dacey (1999: p. 321) suggested that modern creativity research has developed across a range of disciplines as "psychological and contextual influences received more recognition". Furthermore, creativity should not be seen purely in terms of novel ideas but that it is intrinsically bound with the teaching of academic disciplines (Rowlands, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Rowlands (2011) that a truly creative idea, not one that is merely novel but innovative with respect to a background of ideas, does not come out of the void; it must rely on the insights of predecessors. From the educational philosophy, Jaworski (1994) confirms that the accumulation of global and local knowledge contribute to how students conceptualize their views to the world.…”
Section: Introductionmentioning
confidence: 99%